Penentuan Harga Jual UMKM Kandang Anak Ragil dan Kenari by Coxy melalui Analisis HPP dengan Metode Full Costing - Meilida Sofiana, Ervina; Sri Utami, Endang (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
This community service activity aims to analyze the application of production cost calculation using the full costing method. The full costing method covers all cost elements, both variable and fixed. This activity is carried out using a quantitative research approach, where data in the form of numbers is collected or interview results are converted into numerical data. Primary data in this activity is obtained directly from MSMEs through documentation, interviews, and observations. The results of community service activities on two MSMEs, namely Kandang Anak Ragil and Kenari by Coxy, show that both still use simple calculation methods without applying applicable accounting standards to determine the cost of production. In practice, these MSMEs have not calculated all costs incurred during the production process. In addition, both MSMEs tend to use market prices without conducting in-depth analysis when setting selling prices, so that the profits obtained are not in accordance with expectations.